The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1346/ccmn.1980.0280104
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscope Morphology of Deeply Weathered Granite

Abstract: Abstract--Laterite profiles developed from granite in southwestern Australia were studied by scanning electron microscopy. The morphology of soil materials reflects the mineralogy of secondary minerals formed from feldspar. In the saprolite, etched feldspar surfaces are coated with kaolinite or radiating, spherical aggregates of tubular halloysite. In the lower pallid zone these minerals have replaced most of the feldspar. In the upper pallid zone a porous framework has developed consisting mainly of quartz an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 14 publications
1
11
0
2
Order By: Relevance
“…Halloysite mostly occurs as poorly formed tubular crystals which show some evidence of unrolling in the upper saprolite samples. Where halloysite is the dominant alteration product it occurs in felted masses ( Figure 4B) or as radiating spherical aggregates resembling those described by Eswaran and Bin (1978), Keller (1978), Diamond and Bloor (1970), and Gilkes and Suddhiprakarn (1980). Although most of the particles seen in electron micrographs were easily recognized as crystalline kaolinite, halloysite, or gibbsite, some very small (~ 200/k) disc-or sphere-shaped particles were noted, which on the basis of their morphology, could be a noncrystalline material ( Figure 4C).…”
Section: Morphology and Mineralogy Of Alteration Productsmentioning
confidence: 93%
“…Halloysite mostly occurs as poorly formed tubular crystals which show some evidence of unrolling in the upper saprolite samples. Where halloysite is the dominant alteration product it occurs in felted masses ( Figure 4B) or as radiating spherical aggregates resembling those described by Eswaran and Bin (1978), Keller (1978), Diamond and Bloor (1970), and Gilkes and Suddhiprakarn (1980). Although most of the particles seen in electron micrographs were easily recognized as crystalline kaolinite, halloysite, or gibbsite, some very small (~ 200/k) disc-or sphere-shaped particles were noted, which on the basis of their morphology, could be a noncrystalline material ( Figure 4C).…”
Section: Morphology and Mineralogy Of Alteration Productsmentioning
confidence: 93%
“…Previous electron microscopic studies frequently reported the coexistence of both minerals in weathering profiles (Keller 1977;Gilkes et al 1980;Keller et al 1980;Banfield 1985;Banfield and Eggleton 1990). Their coexistence is of interest because they have similar chemistry and structure.…”
Section: Introductionmentioning
confidence: 97%
“…Halloysite and kaolinite are the most common kaolin minerals in these weathering environments (Keller, 1977;Gilkes et al, 1980;Keller et aL, 1980;Banfield and Eggleton, 1990;Schroeder et al, 1997). The common coexistence of these two minerals in the weathering profile attracts much interest because of their chemical and structural similarity.…”
Section: Introductionmentioning
confidence: 99%